Additional Cover. Issue 5 (24th May 2021) - Kronemeijer, Auke Jisk; Peeters, Bart; de Haas, Gerard; Verbeek, Roy; Bel, Thijs; van de Laar, Robert; Ugalde Lopez, Leslye Astrid; Peters, Laurens C. J. M.; Gelinck, Gerwin H.
Abstract : The cover image is based on the Special Section Paper Active‐matrix mesh electronics thin‐film‐transistor arrays for biometrics‐under‐display and biomedical applications by Auke Jisk Kronemeijer et al., https://doi.org/10.1002/jsid.1025 .